OPTIMALISASI PENGGUNAAN SISTEM INFORMASI KEUANGAN DAERAH PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KABUPATEN BIAK NUMFOR - Djamil Hasim,; Yanes Mirino,; Rijal, (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The purpose of this study was to determine the optimization of the use of the regional financial information system (SIKD) at the Regional Financial Management Agency (BPKD) in Biak Numfor Regency. This research method uses a case study technique with qualitative descriptive research, data collection techniques through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Regional Financial Information System at the Regional Financial Management Agency in the Biak Numfor region has not been implemented optimally where the System Quality indicator is inadequate where the existing facilities are inadequate so that it becomes a factor hindering the regional financial management process, on the Information Quality indicator it appears sufficient However, improvements still need to be made so that the accuracy and timely delivery of information is more optimal, the Service Quality indicator is seen to be not optimal due to the lack of network quality support in the use of regional financial information systems, then the User Satisfaction indicator is seen to be quite optimal because it is easily accessible and responded, this is based on previous experience in running existing application systems.